LBL Seabed Datum Transfer without Acoustic Ray Correction - Li Cui, Yue Wu, Yilan Chen, Jisheng Ding, Fangqi Wang, Long Yang, Yikai Feng (Forest Chemicals Review, 2022)
This paper focuses on LBL seabed datum transfer as the research object. Long Baseline underwater acoustic positioning system (LBL) is applied to locating various submersible vehicles. Transmission of the LBL seabed datum is one of the key factors, which have impact on positioning accuracy of system. With the development of marine science and engineering technology, it has become a basic problem to transmit water surface or land datum to seabed accurately by use of LBL in deep-sea scientific research. Traditional seabed datum transfer method is of low accuracy, which adopts slant range observation and linear navigation observation or uses USBL/SBL directly. Based on ray theory, this paper combined the underwater acoustic broadband signals ranging technology with Global Navigation Satellite System (GNSS) precise positioning technology effectively. By using circular voyage to observe symmetrically and using classic adjustment theory to eliminate sound velocity systematic error, this paper realized the transmission with high precision between the seabed surveying and mapping datum and the land surveying and mapping datum without velocity of sound correcting. Experimental results showed that the accuracy of the reference point on the seabed can reach centimeter order, which is equal to the CNSS positioning accuracy. The proposed method has been verified by the experiment in Songhua Lake.